Teknologi sebagai Sumber Kepuasan: Bukti Kepuasan Baru Media Sosial Tiktok di Kalangan Dewasa Muda - Zulfa, Shofiyah Sausan; Rozaq, Miftahul (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
Technology plays an important role in everyday life, social media has become one of the main sources of satisfaction for young adults. One platform that stands out is TikTok, and the bandwagon is clear evidence of the newfound gratification that technology has generated in these circles. Survey and questionnaire methods were used to collect data from 213 respondents who actively use TikTok. The research results prove that motives have a significant positive effect on user satisfaction, and the use of TikTok social media has a significant positive effect on user satisfaction.